Does Ownership Structure Affect Bank Performance in The Covid-19 Pandemic Period? Evidence From Croatia - Fotova Čiković, Katerina; Keček, Damira; Lozić, Joško (Yugoslav Journal of Operations Research, 2022)
This paper investigates the relationship between bank ownership and efficiency before and after the COVID-19 pandemic in a sample of 20 Croatian commercial banks in the period from 2015 to 2020. The interconnection between these variables is examined with the use of a dynamic data envelopment analysis (window DEA) framework. Other goals are to measure the relative efficiency of Croatian banks in the observed period as well as the evolvement of the banking sector as a whole. The findings reveal that domestic banks outperform by little foreign-owned Croatian banks during the COVID-19 crisis year 2020, but, moreover, domestic and small-sized banks have experienced the least negative impact of COVID-19 in 2020. The results regarding the impact of bank size on bank efficiency are inconsistent and require additional study. The used methodology and the findings of this empirical research could be of interest to academic members, bank management and policymakers. The latter should be especially interested in the results and the resilience of domestic and foreign banks to external shocks, in order to re-examine their current bank policies and the national attitude towards attracting foreign capital in the banking sector.